Aluminum plastic film and preparation method thereof, battery and electric equipment
By applying corrosion-resistant coatings of Ti, Zr and Si elements on aluminum-plastic films, the problem of corrosion of aluminum-plastic films in electrolytes is solved, and the safety performance and service life of the battery are improved.
Patent Information
- Application Number
- CN202411357535.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing aluminum-plastic films are prone to corrosion under the long-term infiltration of the electrolyte, causing the electrolyte to leak liquid, affecting the service life and safety performance of the battery.
Using corrosion-resistant coatings containing Ti elements, Zr elements and Si elements, the corrosion-resistant coatings are formed with the aluminum foil surface to improve the corrosion resistance of the aluminum plastic film, and silane coupling agents and resins are used during the preparation process. material, forming a coating with hydrophobic properties.
It significantly improves the electrolyte corrosion resistance of aluminum-plastic film, extends the service life of the battery, reduces the risk of electrolyte leakage, and improves the safety performance of the battery.
Smart Images

Figure CN119253154A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to an aluminum-plastic film and a preparation method thereof, a battery and an electrical device. Background Art
[0002] At present, aluminum-plastic films are commonly used as packaging materials for secondary batteries. Aluminum-plastic films in related technologies have excellent mechanical properties, heat insulation properties, and moisture resistance, but their electrolyte resistance still needs to be improved. The current aluminum-plastic films will corrode under long-term infiltration of electrolytes, causing electrolyte leakage, threatening the service life and safety performance of the battery. Summary of the invention
[0003] In view of this, the embodiments of the present application provide an aluminum-plastic film and a preparation method thereof, a battery and an electrical device. The aluminum-plastic film can achieve better resistance to electrolyte corrosion, thereby reducing the risk of battery electrolyte leakage, thereby improving the safety performance of the battery and extending its service life.
[0004] A first aspect of an embodiment of the present application provides an aluminum-plastic film, comprising an aluminum foil and a corrosion-resistant coating arranged on at least one surface of the aluminum foil; the corrosion-resistant coating comprises an A element, and the A element is selected from at least one of Ti and Zr elements and Si element.
[0005] The above-mentioned Ti, Zr and Si elements can give the corrosion-resistant coating a certain ability to resist electrolyte corrosion, which is beneficial to improving the safety performance of the battery and extending the service life of the battery. In addition, the Si element can improve the hydrophobicity of the corrosion-resistant coating, reduce the contact angle between the electrolyte and the corrosion-resistant coating, and inhibit the infiltration of the electrolyte into the corrosion-resistant coating, thereby further reducing the corrosion of the electrolyte to it.
[0006] A second aspect of the embodiment of the present application provides a method for preparing an aluminum-plastic film, comprising:
[0007] Mixing a Ti element source and / or a Zr element source, a silane coupling agent and water to obtain a mixture; forming the mixture on at least one side surface of the aluminum foil, and curing to form a corrosion-resistant coating to obtain an aluminum-plastic film;
[0008] The corrosion-resistant coating includes an A element, and the A element is selected from at least one of a Ti element and a Zr element and a Si element.
[0009] The preparation method has simple process, high production efficiency and is suitable for large-scale industrial production.
[0010] A third aspect of the embodiments of the present application provides a battery, comprising an aluminum-plastic film; the aluminum-plastic film is the aluminum-plastic film provided in the first aspect of the embodiments of the present application, or the aluminum-plastic film is obtained by the preparation method of the aluminum-plastic film provided in the second aspect of the embodiments of the present application.
[0011] A fourth aspect of the embodiments of the present application provides an electrical device, comprising the battery provided in the third aspect of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1A A schematic diagram of the structure of an aluminum-plastic film provided in one embodiment of the present application;
[0013] Figure 1B A schematic diagram of the structure of an aluminum-plastic film provided in another embodiment of the present application;
[0014] Figure 2 A schematic structural diagram of an aluminum-plastic film provided in yet another embodiment of the present application;
[0015] Figure 3 Schematic diagram of possible bonding modes between the corrosion-resistant coating and aluminum foil interface.
[0016] Explanation of the reference numerals: 1 - aluminum-plastic film; 10 - aluminum foil; 20 - corrosion-resistant coating; 201 - first corrosion-resistant coating; 202 - second corrosion-resistant coating; 203 - third corrosion-resistant coating; 30 - nylon layer; 40 - heat-sealing layer. DETAILED DESCRIPTION
[0017] At present, aluminum-plastic film is a commonly used packaging material for secondary batteries. In the production process of secondary batteries, aluminum-plastic film is generally used to encapsulate the positive electrode, diaphragm, negative electrode and other battery components stacked in layers to obtain a dry battery cell, and then electrolyte is injected into the dry battery cell to obtain a battery cell, and then a secondary battery is obtained. Although the existing aluminum-plastic film has good mechanical properties and thermal insulation properties, its resistance to electrolyte corrosion is relatively weak. During the injection of the electrolyte, if the electrolyte drips onto the surface of the aluminum-plastic film, the dripping electrolyte will corrode the aluminum-plastic film, causing the corresponding position to become a weak position in the service process of the aluminum-plastic film, which seriously threatens the safety performance of the battery; in addition, the inner surface of the aluminum-plastic film is infiltrated by the electrolyte for a long time, which will also corrode, and in severe cases, it will cause electrolyte leakage, affecting the service life and safety performance of the battery.
[0018] In order to solve the above technical problems, the present application embodiment provides an aluminum-plastic film, please refer to Figure 1A to Figure 1B The aluminum-plastic film 1 includes an aluminum foil 10 and a corrosion-resistant coating 20 disposed on at least one side of the aluminum foil 10; the corrosion-resistant coating 20 includes an A element, and the A element is selected from at least one of a Ti element and a Zr element and an Si element. In the embodiment of the present application, EDS can be used to characterize the presence of the A element.
[0019] In the embodiment of the present application, the corrosion-resistant coating 20 may be provided on one side of the aluminum foil 10, or may be provided on both sides of the aluminum foil 10. In some embodiments of the present application, the corrosion-resistant coating 20 is provided on both sides of the aluminum foil 10.
[0020] The above-mentioned Ti, Zr and Si elements can give the corrosion-resistant coating a certain ability to resist electrolyte corrosion, which is beneficial to improving the safety performance of the battery and extending the service life of the battery. In addition, the Si element can improve the oleophobicity of the corrosion-resistant coating, reduce the contact angle between the electrolyte and the corrosion-resistant coating, and inhibit the infiltration of the electrolyte into the corrosion-resistant coating, thereby further reducing the corrosion of the electrolyte to it; in addition, the Si element is also beneficial to improving the flexibility of the corrosion-resistant coating.
[0021] In some embodiments of the present application, the corrosion-resistant coating further includes a resin. The resin has excellent compactness and certain mechanical properties; in addition, it is understandable that the corrosion-resistant coating contains a resin, which can give the corrosion-resistant coating a higher compactness and further enhance the corrosion-resistant coating's ability to resist electrolyte corrosion. In some specific embodiments, the resin includes but is not limited to one or more of acrylic resin, polyurethane resin, fluorocarbon resin and epoxy resin. The chemical stability, mechanical properties and sealing properties of the above-mentioned resin materials are all excellent. In addition, the flexibility of the above-mentioned resin is good, which is conducive to improving the flexibility of the corrosion-resistant coating. In the embodiments of the present application, the presence of the resin can be characterized by methods such as nuclear magnetic resonance and infrared spectroscopy. In some specific embodiments, the above-mentioned resin is a cross-linked resin with a cross-linked network structure. In the preparation process of the corrosion-resistant coating, in order to improve the curing degree and curing rate of the resin and increase the fineness of the coating, rare earth additives are also added to the raw materials. Therefore, in some embodiments of the present application, the corrosion-resistant coating also includes a rare earth additive or its reactant. Specifically, the rare earth additive can be, for example, one or more of rare earth salts such as cerium nitrate, cerium acetate, lanthanum nitrate, lanthanum acetate, and dysprosium acetate.
[0022] In some embodiments of the present application, the A element and the resin are evenly dispersed in the corrosion-resistant coating, so that the corrosion-resistant coating has good uniformity and the comprehensive protective performance of the aluminum-plastic film is better.
[0023] In some embodiments of the present application, a chemical bond is formed between the A element and the resin. In this way, the corrosion-resistant coating has good stability, is not prone to deterioration, etc., and is more conducive to extending the service life of the aluminum-plastic film. In some specific embodiments, the above-mentioned chemical bonds include but are not limited to one or more of COA bonds and CA bonds. Among them, the COA bond can be, for example, one or more of CO-Si, CO-Zr, and CO-Ti bonds, and the CA bond can be, for example, one or more of C-Si bonds, C-Zr bonds, and C-Ti bonds. In some specific embodiments, the corrosion-resistant coating includes a compound containing an AOA bond; a chemical bond is formed between the compound containing an AOA bond and the resin; the AOA bond includes, at least one of Si-O-Ti bonds, Si-O-Zr bonds, and Si-O-Si bonds. In other specific embodiments, when the A element includes Si, Ti, and Zr elements at the same time, the above-mentioned AOA bond also includes at least one of Ti-O-Ti bonds, Ti-O-Zr bonds, and Zr-O-Zr bonds. In this way, it is more conducive to improving the corrosion resistance of the corrosion-resistant coating.
[0024] In some embodiments of the present application, the mass proportion of the resin in the corrosion-resistant coating is 5wt% to 15wt%. In this way, it is beneficial to ensure the mechanical properties and density of the corrosion-resistant coating, and it will not occupy the share of the A element, thereby benefiting the comprehensive performance of the corrosion-resistant coating. Specifically, the mass proportion of the resin in the corrosion-resistant coating can be, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc.
[0025] In some embodiments of the present application, the corrosion-resistant coating has at least one of a Si-O-Si bond, a Si-O-Ti bond, and a Si-O-Zr bond, and a hydrogen bond is formed between the aluminum foil and the corrosion-resistant coating (see Figure 3 ). It is understandable that in some embodiments, during the preparation of the aluminum-plastic film, the aluminum foil is pretreated to have hydroxyl groups on its surface. When the corrosion-resistant coating has any one of Si-O-Si bonds, Si-O-Ti bonds, and Si-O-Zr bonds, the above chemical bonds can form hydrogen bonds with the hydroxyl groups of the aluminum foil, thereby forming hydrogen bonds between the corrosion-resistant coating and the aluminum foil, thereby improving the interfacial bonding strength between the corrosion-resistant coating and the aluminum foil, and further improving the structural stability of the aluminum-plastic film.
[0026] In some embodiments of the present application, the corrosion-resistant coating contains silanol groups, which react with hydroxyl groups on the surface of the aluminum foil to form Si-O bonds, thereby forming Si-O bonds between the corrosion-resistant coating and the aluminum foil. The chemical bond has a stronger binding force, which is more conducive to improving the interface bonding force between the corrosion-resistant coating and the aluminum foil.
[0027] In some embodiments of the present application, the mass proportion of Si element in the corrosion-resistant coating is 0.28wt% to 2.5wt%. In this way, it is beneficial to optimize the interface bonding force between the corrosion-resistant coating and the aluminum foil and improve its oleophobic performance, and it will not squeeze out the share of other elements. Specifically, the mass proportion of Si element in the corrosion-resistant coating can be, for example, 0.3wt%, 0.6wt%, 0.9wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.1wt%, 2.5wt%.
[0028] In some embodiments of the present application, element A includes element Zr. That is, the corrosion-resistant coating must contain element Zr and element Si. In particular, the presence of element Zr is more conducive to improving the corrosion resistance of the corrosion-resistant coating, and can also simultaneously improve the wear resistance of the corrosion-resistant coating, reduce external mechanical damage to the battery, and is more conducive to improving the safety performance and service life of the battery. In some specific embodiments, the mass proportion of the Zr element in the corrosion-resistant coating is 0.3wt% to 1.5wt%. Specifically, the mass proportion of the Zr element in the corrosion-resistant coating can be, for example, 0.3wt%, 0.6wt%, 0.9wt%, 1.2wt%, 1.5wt%, etc.
[0029] In some embodiments of the present application, the mass proportion of the resin in the corrosion-resistant coating is 5wt% to 15wt%; the mass proportion of the Si element in the corrosion-resistant coating is 0.28wt% to 2.5wt%, and the mass proportion of the Zr element in the corrosion-resistant coating is 0.3wt% to 1.5wt%. In this way, the corrosion-resistant coating has excellent oleophobicity, strong resistance to electrolyte corrosion, good wear resistance, and is also conducive to ensuring a high interface bonding force between the corrosion-resistant coating and the aluminum foil.
[0030] Consider that in some cases, the wear resistance of the corrosion-resistant coating is not required to be high. For example, in the application process of the aluminum-plastic film, the side facing the battery element is the inner surface, and the inner surface does not require high wear resistance. At this time, the Zr element may be contained less or not. Therefore, in other embodiments of the present application, the A element includes the Si element and the Ti element. Compared with the Si element, the Ti element has a better effect on improving the corrosion resistance of the corrosion-resistant coating. In some specific embodiments, the mass proportion of the resin in the corrosion-resistant coating is 5wt% to 15wt%; the mass proportion of the Si element in the corrosion-resistant coating is 0.28wt% to 2.5wt%, and the mass proportion of the Ti element in the corrosion-resistant coating is 1.27wt% to 3wt%; the mass proportion of the Zr element in the corrosion-resistant coating is 0.3wt% to 1.5wt%;
[0031] In some further specific embodiments, considering the comprehensive performance of the corrosion-resistant coating, the A element includes Si element, Ti element and Zr element.
[0032] It can be understood that the aluminum-plastic film includes a first surface and a second surface that are arranged oppositely. Considering the use requirements, in some embodiments of the present application, the aluminum-plastic film includes multiple corrosion-resistant coatings, and the multiple corrosion-resistant coatings include a first corrosion-resistant coating and a second corrosion-resistant coating; wherein the first corrosion-resistant coating is arranged on the first surface, and the second corrosion-resistant coating is arranged on the above-mentioned second surface. That is, the aluminum-plastic film includes a first corrosion-resistant coating, an aluminum foil, and a second corrosion-resistant coating that are stacked. In this way, when the aluminum-plastic film is used in a secondary battery, it can reduce the impact caused by the electrolyte dripping on the surface of the aluminum-plastic film during the electrolyte injection process, and can also reduce the corrosion of the aluminum-plastic film by the electrolyte contained in the battery. In combination with the above-mentioned use scenarios, in some embodiments of the present application, the first corrosion-resistant layer includes Zr elements, and the mass content of Zr elements in the first corrosion-resistant layer is greater than the mass content of Zr elements in the second corrosion layer; at this time, there are two situations: 1) the second corrosion-resistant layer does not contain Zr elements; 2) the second corrosion-resistant layer also contains Zr elements; technicians in the field can determine according to production costs and use requirements.
[0033] In some specific embodiments, the first corrosion-resistant coating includes Zr, Ti and Si; in the first corrosion-resistant coating, the mass proportion of Zr is 0.3wt% to 1.5wt%, the mass proportion of Ti is 1.27wt% to 3wt%, and the mass proportion of Si is 0.28wt% to 2.5wt%. At this time, in some specific embodiments, the mass proportion of resin in the first corrosion-resistant coating is 5wt% to 15wt%. In this way, when the above-mentioned aluminum-plastic film is applied to the battery, the above-mentioned first corrosion-resistant coating is suitable for forming the surface of the aluminum-plastic film away from the battery element. Specifically, in the first corrosion-resistant layer, the mass proportion of the Zr element can be, for example, 0.3wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, etc.; the mass proportion of the Ti element can be, for example, 1.3wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc.; the mass proportion of the Si element can be, for example, 0.3wt%, 0.6wt%, 0.9wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.1wt%, 2.5wt%, etc.; the mass proportion of the resin can be, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc.
[0034] In some specific embodiments, the second corrosion-resistant coating includes Ti and Si elements, and optionally Zr elements; in the second corrosion-resistant coating, the mass proportion of Zr elements is less than or equal to 1.2wt%, the mass proportion of Ti elements is 1.27wt% to 3wt%, and the mass proportion of Si elements is 0.28wt% to 2.5wt%. At this time, in some specific embodiments, the mass proportion of resin in the second corrosion-resistant coating is 5wt% to 15wt%. In this way, when the above-mentioned aluminum-plastic film is applied to the battery, the above-mentioned second corrosion-resistant coating is suitable for forming the surface of the aluminum-plastic film facing the battery element. It should be noted that in some embodiments, for cost considerations, the second corrosion-resistant coating may not contain Zr elements. Specifically, in the second corrosion-resistant coating, the mass proportion of Zr element can be, for example, 0wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%; the mass proportion of Ti element can be, for example, 1.3wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc.; the mass proportion of Si element can be, for example, 0.3wt%, 0.6wt%, 0.9wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.1wt%, 2.5wt%, etc.; the mass proportion of resin can be, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc. At this time, considering that the second corrosion-resistant coating has a longer contact time with the electrolyte, a wider contact surface, and a higher requirement for corrosion resistance, the thickness of the second corrosion-resistant coating is 20μm-30μm. Specifically, the thickness of the second corrosion-resistant layer may be, for example, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, etc.
[0035] In some embodiments of the present application, a nylon layer is also provided between the first corrosion-resistant coating and the aluminum foil. In this way, it is beneficial to improve the heat resistance and tear resistance of the aluminum-plastic film, and is more conducive to the performance of the battery. The parameters such as the material and thickness of the above-mentioned nylon layer can be materials and thicknesses well known to technicians in the field, and this application is not limited to this. Specifically, in some embodiments, the thickness of the nylon layer can be, for example, 10μm-30μm, and the material of the nylon layer can be, for example, nylon-6, or a composite of nylon-6 and PET, but is not limited thereto. Specifically, the thickness of the nylon layer can be, for example, 10μm, 12μm, 15μm, 20μm, 25μm, 30μm, etc.
[0036] In some embodiments of the present application, the first corrosion-resistant coating is connected to the nylon layer through an adhesive layer. The material of the adhesive layer includes, but is not limited to, one or more of polyurethane adhesives, acrylic adhesives, epoxy adhesives, etc. In some specific embodiments, the thickness of the adhesive layer may be, for example, 2 μm-5 μm. Specifically, the thickness of the adhesive layer may be, for example, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0037] In some embodiments of the present application, a heat-sealing layer is provided on the surface of the second corrosion-resistant coating facing away from the aluminum foil. Specifically, the heat-sealing layer can be any heat-sealing layer known to technicians in the field. For example, the material of the heat-sealing layer includes cast polypropylene (CPP), and the thickness of the heat-sealing layer can be 40μm-80μm. In some specific embodiments, the heat-sealing layer is formed on the surface of the second corrosion-resistant coating by hot pressing and compounding, that is, the second corrosion-resistant coating is in direct contact with the heat-sealing layer. Specifically, the thickness of the heat-sealing layer can be, for example, 40μm, 45μm, 50μm, 55μm, 60μm, 70μm, 80μm, etc.
[0038] In some embodiments of the present application, the thickness of the aluminum foil is 30 μm-60 μm. It is understandable that aluminum is easily oxidized, and the surface of the aluminum foil has a thin layer of aluminum oxide. Specifically, the thickness of the aluminum foil can be, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, etc.
[0039] In some embodiments of the present application, in order to further improve the corrosion resistance of the aluminum-plastic film, the aluminum-plastic film further includes a third corrosion-resistant coating, and the third corrosion-resistant coating is disposed between the aluminum foil and the nylon layer. Figure 2 The aluminum-plastic film 1 includes a first corrosion-resistant coating 201, a nylon layer 30, a third corrosion-resistant coating 203, an aluminum foil 10, a second corrosion-resistant coating 202, and a heat-sealing layer 40 which are stacked in sequence. In some specific embodiments, the above-mentioned adhesive layer (not shown in the figure) is arranged between the first corrosion-resistant coating 201 and the nylon layer 30, and between the third corrosion-resistant coating 203 and the nylon layer 30. Similarly, the thickness of the third corrosion-resistant coating is 20μm-30μm. Specifically, the thickness of the third corrosion-resistant layer can be, for example, 20μm, 22μm, 25μm, 28μm, 30μm, etc.
[0040] In order to reduce the difficulty of preparing the corrosion-resistant coating, in some embodiments of the present application, a small amount of additives is added to the raw materials of the corrosion-resistant coating. The additives may remain in the corrosion-resistant coating, but will not affect the performance of the corrosion-resistant coating. In some specific embodiments, the additives include defoamers and leveling agents, and the defoamers and leveling agents are commonly used defoamers and leveling agents for resin materials. Therefore, in some embodiments of the present application, the corrosion-resistant coating also includes the above-mentioned additives.
[0041] In some embodiments of the present application, a catalyst is also added during the preparation of the corrosion-resistant coating to adjust the pH value of the hydrolysis environment involved in the preparation of the corrosion-resistant coating and to adjust the hydrolysis reaction activity of the sol. The catalyst includes but is not limited to one or more of glacial acetic acid, formic acid, nitric acid, and phosphoric acid.
[0042] The present application also provides a method for preparing a corrosion-resistant coating, which can be used to prepare the aluminum-plastic film provided in the present application, comprising:
[0043] S1, mixing a silane coupling agent, a Ti element source and / or a Zr element source and water to obtain a mixture;
[0044] S2. Forming the mixture on at least one side surface of the aluminum foil, curing to form a corrosion-resistant coating, and obtaining an aluminum-plastic film; the corrosion-resistant coating comprises an A element, and the A element is selected from at least one of a Ti element and a Zr element and a Si element.
[0045] The silane coupling agent can catalyze the hydrolysis of the Ti element source and / or the Zr element source, and the Si element will also be released after the silane coupling agent participates in the catalysis, thereby forming a corrosion-resistant coating. The above preparation method is simple and easy to implement, has strong process reliability, high production efficiency, and is suitable for large-scale industrial production.
[0046] In some embodiments of the present application, based on the mass of the mixture, the mass proportion of the silane coupling agent is 15.2wt%-27wt%. Specifically, in the mixture, the mass proportion of the silane coupling agent can be, for example, 15.2wt%, 16wt%, 18wt%, 20wt%, 22wt%, 25wt%, 27wt%, etc.
[0047] In some embodiments of the present application, based on the mass of the mixture, the mass proportion of water is 2.3wt%-13.5wt%. Specifically, the mass proportion of water in the mixture can be, for example, 2.3wt%, 2.5wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 13wt%, 13.5wt%, etc.
[0048] In some embodiments of the present application, based on the mass of the mixture, the sum of the mass of the Ti element source and the Zr element source accounts for 38wt%-63wt% of the mass of the mixture. Specifically, in the mixture, the sum of the mass of the Ti element source and the Zr element source may account for 38wt%, 40wt%, 42wt%, 45wt%, 48wt%, 50wt%, 52wt%, 55wt%, 58wt%, 60wt%, 62wt%, 63wt%, etc.
[0049] In some embodiments of the present application, the Ti element source includes one or more of tetrabutyl titanate, tetraethyl titanate, and tetraisopropyl titanate. The above substances can be hydrolyzed to form titanium sol. For example, the chemical formula of complete hydrolysis of tetrabutyl titanate is as follows, wherein R is butyl:
[0050] Of course, the hydrolysis of the Ti element source is also accompanied by a condensation reaction, specifically, Ti-OH reacts with Ti-OH to form a Ti-O-Ti bond, so that the corrosion-resistant coating finally obtained includes a compound containing a Ti-O-Ti bond.
[0051] In some embodiments of the present application, the Zr element source includes one or more zirconium compounds that can synthesize olefin functional groups, such as zirconium n-propoxide (tetra-n-propyl zirconate), zirconium n-butoxide, zirconium tert-butoxide, and zirconium tetraethoxide. The above Zr element source can be hydrolyzed to form a zirconium sol. Specifically, taking zirconium n-propoxide as an example, the chemical formula of the complete hydrolysis of the Zr element source is shown as follows:
[0052] Of course, the hydrolysis process of the Zr element source is also accompanied by a condensation reaction, specifically, Zr-OH reacts with Zr-OH to form a Zr-O-Zr bond, so that the corrosion-resistant coating finally obtained includes a compound containing a Zr-O-Zr bond.
[0053] In some embodiments of the present application, the above step S1 includes: mixing a silane coupling agent, a Ti element source and / or a Zr element source, water and a resin raw material to obtain a mixture. Specifically, the resin raw material can be the resin itself, or it can be a prepolymer or even a monomer for formation. In this case, the above step S1 includes: mixing a silane coupling agent, a Ti element source and / or a Zr element source, a resin raw material and water includes:
[0054] S101, mixing a Ti element source, water and a silane coupling agent to obtain a Ti sol; and / or, mixing a Zr element source, water and the silane coupling agent to obtain a Zr sol;
[0055] S102, mixing the Ti sol and the resin raw material; or, mixing the Zr sol and the resin raw material; or, first mixing the Ti sol and the Ti sol to obtain a Zr-Ti composite sol, and then mixing the Zr-Ti composite sol and the resin raw material to obtain the mixture. The silane coupling agent can catalyze the hydrolysis of the Ti element source and / or the Zr element source, and the generated hydrolysis product can be dispersed in the resin raw material, and the Si element will also be released after the silane coupling agent participates in the catalysis, and dispersed in the resin raw material together with the Ti element and / or the Zr element, and finally forming a corrosion-resistant coating.
[0056] In some embodiments of the present application, the mass of the resin raw material accounts for 5wt%-15wt% of the mass of the mixture. Specifically, the mass of the resin raw material can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc. of the mass of the mixture.
[0057] In step S102, after the Ti sol and the Zr sol are mixed, the Ti-OH bond and the Zr-OH bond may react to generate a Ti-O-Zr bond, so that the corrosion-resistant coating finally obtained includes a compound containing a Ti-O-Zr bond. Of course, at this time, Zr-OH and Zr-OH may react to generate a Zr-O-Zr bond, or Ti-OH and Ti-OH may react to generate a Ti-O-Ti bond. Therefore, at this time, the corrosion-resistant coating finally obtained may include a compound containing a Ti-O-Zr bond and at least one chemical bond of a Zr-O-Zr bond and / or a Ti-O-Ti bond.
[0058] In some embodiments of the present application, the above step S1 includes: mixing a silane coupling agent, a Ti element source and / or a Zr element source, water and a first silicon source; the first silicon source is selected from one or more of tetraethyl orthosilicate, silicate, and organosilane polymer. In some specific embodiments, the first silicon source accounts for 3wt% to 9.5wt% of the mass of the mixture. It should be noted that although the silane coupling agent can provide silicon elements for the final corrosion-resistant coating, it is only for the convenience of description here. Therefore, when discussing the relevant parameters and properties of the first silicon source, the silane coupling agent is not included. At this time, the preparation of the aluminum-plastic film includes:
[0059] S111, mixing a Ti element source, water and the silane coupling agent to obtain a Ti sol; mixing a Zr element source, water and the silane coupling agent to obtain a Zr sol; mixing a Si element source, water and the silane coupling agent to obtain a Si sol;
[0060] S112, first mixing the Ti sol, the Si sol and the Ti sol to obtain a Zr-Ti-Si composite sol, and then mixing the Zr-Ti-Si composite sol and the resin raw material to obtain the mixture;
[0061] S2, forming the mixture on at least one side surface of the aluminum foil, and curing it to form a corrosion-resistant coating to obtain an aluminum-plastic film.
[0062] In some embodiments of the present application, in step S112, when preparing Ti sol, it is also necessary to add alcohol reagents such as ethanol (for example, anhydrous ethanol) so that the inorganic components can be more dispersed, and the hydrolysis rate of the inorganic components in deionized water can be slowed down to prevent condensation into blocks. Specifically, the preparation of Ti sol includes: mixing Ti element source, water, silane coupling agent and ethanol to obtain a first mixture, stirring, and obtaining Ti sol. Wherein, based on the mass of the first mixture, the mass proportion of water is 3wt% to 15wt%, the mass proportion of silane coupling agent is 20wt% to 30wt%, the mass proportion of ethanol is 25wt% to 40wt%, and the mass proportion of Ti element source is 30wt% to 40wt%. In some specific embodiments, the above stirring time is 50min-90min. In this way, it is conducive to the full hydrolysis of the Ti element source, and the final Ti element can be improved to form a chemical bond with the resin, specifically, it is conducive to the formation of a chemical bond between the Ti element and the resin, so as to optimize the quality of the final corrosion-resistant coating.
[0063] In some specific embodiments, a catalyst is also required to be added when preparing the Ti sol; the mass proportion of the catalyst in the first mixture is 0.3wt% to 1wt%. The catalyst can adjust the pH of the hydrolysis environment involved in the preparation process of the corrosion-resistant coating and adjust the hydrolysis reaction activity of the sol, and the catalyst includes but is not limited to one or more of glacial acetic acid, formic acid, nitric acid, and phosphoric acid.
[0064] Similarly, in some embodiments of the present application, in step S112, ethanol (for example, anhydrous ethanol) also needs to be added when preparing Zr sol. Specifically, the preparation of Zr sol includes: mixing Zr element source, water, silane coupling agent and ethanol to obtain a first mixture, stirring, and obtaining Zr sol. Wherein, based on the mass of the first mixture, the mass proportion of water is 3wt% to 15wt%, the mass proportion of silane coupling agent is 20wt% to 30wt%, the mass proportion of ethanol is 25wt% to 40wt%, and the mass proportion of Zr element source is 20wt% to 30wt%. In this way, it is conducive to the full hydrolysis of Zr element source, which can improve the final chemical bond between Zr element and resin, specifically, it is conducive to the formation of chemical bond between Zr element and resin, so as to optimize the quality of the final corrosion-resistant coating. Similarly, the above stirring time is 50min-90min. In some embodiments, when preparing Si sol, the aforementioned catalyst is added to the system.
[0065] Similarly, in some embodiments of the present application, in step S112, ethanol (for example, anhydrous ethanol) also needs to be added when preparing Si sol. Specifically, the preparation of Si sol includes: mixing a first silicon source, water, a silane coupling agent and ethanol to obtain a first mixture, stirring, and obtaining Si sol. Among them, based on the mass of the first mixture, the mass proportion of water is 3wt% to 15wt%, the mass proportion of the silane coupling agent is 20wt% to 30wt%, the mass proportion of ethanol is 25wt% to 40wt%, and the mass proportion of the first silicon source is 20wt%-30wt%. Similarly, the above stirring time is 50min-90min. In some embodiments, when preparing Si sol, the aforementioned catalyst is added to the system.
[0066] In some embodiments of the present application, in step S112, the following reaction may occur after the Ti sol, Si sol and Zr sol are mixed:
[0067]
[0068] Thus, the compounds included in the Zr-Ti-Si composite sol include Ti-O-Zr bonds and Si-O-Ti bonds; it can be understood that the above formula is only one of the multiple reactions that may occur, and is only an example; specifically, it may also be a reaction between two Zr-OH bonds, a reaction between two Ti-OH bonds, and a reaction between two Si-OH bonds, so the compounds included in the final Zr-Ti-Si composite sol may include one or more of Ti-O-Zr bonds, Si-O-Ti, Si-O-Zr bonds, Zr-O-Zr, Ti-O-Ti bonds, and Si-O-Si bonds. And the above compounds can further form chemical bonds with organic raw materials (e.g., resins).
[0069] It is understandable that in the embodiments of the present application, the components and component contents in the corrosion-resistant coating can be adjusted as needed, so its preparation can also be adjusted accordingly according to the parameters of the expected corrosion-resistant coating. The relative amount of Ti sol, Zr sol, Si sol, composite sol (including any two of Ti sol, Zr sol, Si sol, or Ti-Zr-Si sol) and resin raw material (e.g., resin) can be selected according to the expected component content. In some specific embodiments, titanium sol can be slowly added to silica sol, stirred evenly to obtain silicon-titanium composite sol, and then zirconium sol intermediate is slowly added to the aforementioned prepared silicon-titanium sol, stirred evenly to obtain Zr-Ti-Si composite sol. The amount of titanium sol, silica sol and zirconium sol can be selected as needed. In some cases, the mass ratio of titanium sol, silica sol and zirconium sol is (1.143-3): 1: (0.286-1.5).
[0070] In some embodiments of the present application, in the above step S112, the resin and the Zr-Ti-Si composite sol are mixed in a mass ratio of 1:(5-18). In this way, the corrosion-resistant coating formed has excellent corrosion resistance, mechanical properties and hydrophobic properties.
[0071] In some embodiments of the present application, in the above step S112, in order to solidify the resin raw material and even form a cross-linked network structure, the mixture also includes a curing agent, and the mass ratio of the curing agent to the resin raw material is (0.3-1.0): (5-15). In the embodiment of the present application, the above curing agent can be determined according to the type of the selected resin raw material, and can be a curing agent suitable for the corresponding resin raw material that is well known to technicians in the resin field, for example, a thermal curing agent, a light curing agent, etc. In some specific embodiments, a light curing agent is selected; in this case, the curing mentioned in step S2 is a light curing process, and the specific parameters of the light curing process can be determined according to the selected resin and curing agent, and the present application does not limit this.
[0072] Furthermore, in some specific embodiments, the mixture further includes rare earth additives and other additives, including leveling agents and defoamers, etc. The mass ratio of the rare earth additive to the resin is 1:(1-7.9), and the mass ratio of the other additives to the resin is 1:(1.1-16.7).
[0073] In some embodiments of the present application, in step S2, before the mixture is formed on the surface of the aluminum foil, the aluminum foil is also roughened. The roughening process can be any roughening process known in the art.
[0074] In some embodiments of the present application, in step S2, the process of forming the mixture on the surface of the aluminum foil includes coating. The coating process can be any parameters well known to those skilled in the art.
[0075] It is understandable that the aluminum foil has a first surface and a second surface disposed opposite to each other in the thickness direction. In some embodiments of the present application, in order to further optimize the comprehensive performance of the aluminum-plastic film, a nylon layer, a heat-sealing layer, etc. are also formed in the aluminum-plastic film.
[0076] In some specific embodiments, step S2 includes:
[0077] S21, sequentially forming a nylon layer, a first bonding layer, and a first corrosion-resistant coating on a first surface of the aluminum foil;
[0078] A second corrosion-resistant coating is formed on the second surface of the aluminum foil, and the surface of the second corrosion-resistant coating is hot-pressed and composited to form the aforementioned heat-sealing layer.
[0079] In some specific embodiments of the present application, in step S21, before forming the nylon layer, the process also includes: sequentially forming a third corrosion-resistant coating and a second bonding layer on the first surface of the aluminum foil.
[0080] The embodiment of the present application also provides a battery, comprising the aluminum-plastic film provided in the embodiment of the present application. Since the aluminum-plastic film provided in the embodiment of the present application is used as packaging, the battery has higher safety performance and longer service life.
[0081] In some embodiments of the present application, the battery further includes a positive electrode, a negative electrode and an electrolyte contained in the aluminum-plastic film.
[0082] In some embodiments of the present application, when the aluminum-plastic film includes a first corrosion-resistant coating, a nylon layer, an aluminum foil, and a second corrosion-resistant coating stacked in sequence, the first corrosion-resistant coating is arranged on a side away from the positive electrode, the negative electrode, and the electrolyte. In some specific embodiments, there is also a bonding layer between the first corrosion-resistant coating and the nylon layer. Further, a third corrosion-resistant coating is also arranged between the nylon layer and the aluminum foil, and the third corrosion-resistant coating is arranged close to the aluminum foil.
[0083] In some embodiments of the present application, the above-mentioned battery can be any alkali metal ion battery such as a lithium ion battery, a sodium ion battery, a magnesium ion battery, etc.
[0084] In some embodiments of the present application, the battery is a liquid battery using a liquid electrolyte, but it can also be a solid-state battery or a semi-solid-state battery.
[0085] In some embodiments of the present application, the positive electrode, negative electrode, and electrolyte may be any known positive electrode, negative electrode, and electrolyte suitable for the corresponding battery. Of course, the battery may also include other battery elements for forming an electron path and an ion path.
[0086] The present application also provides an electric device, including the battery provided in the present application. Since the battery provided in the present application is used to power the electric device, the electric device has a better market prospect.
[0087] In some embodiments of the present application, the above-mentioned electrical equipment includes but is not limited to vehicles, or 3C electronic consumer products such as mobile phones, laptops, tablet computers, smart watches, etc.
[0088] The technical solution of the present application is described in detail below with multiple embodiments.
[0089] Example 1
[0090] (1) Preparation of silica sol: Silane coupling agent, tetraethyl orthosilicate, anhydrous ethanol, deionized water, and a catalyst (specifically glacial acetic acid) in a mass ratio of 29.5:20:40:10:0.5 were mixed evenly, and stirred for hydrolysis for 60 minutes to obtain silica sol.
[0091] Preparation of titanium sol: silane coupling agent, tetrabutyl titanate, anhydrous ethanol, deionized water, and a catalyst (specifically glacial acetic acid) in a mass ratio of 29.5:30:30:10:0.5 were uniformly mixed, and the titanium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0092] Preparation of zirconium sol: silane coupling agent, zirconium n-propoxide, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:20:40:10:0.5, and the zirconium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0093] (2) Preparation of silicon-titanium-zirconium composite sol: Weigh titanium sol, silica sol and zirconium sol in a mass ratio of 60:30:10, slowly add the titanium sol to the silica sol, stir evenly to obtain silicon-titanium sol, then slowly add the zirconium sol to the silicon-titanium sol prepared above, stir evenly to obtain silicon-titanium-zirconium composite sol.
[0094] (3) Weighing a silicon titanium zirconium sol, a rare earth additive (specifically cerium nitrate), an acrylic resin, and an auxiliary agent (specifically a defoamer and a leveling agent) in a mass ratio of 85:4:10:1, slowly adding the rare earth additive, acrylic resin, and auxiliary agent into the silicon titanium sol, stirring for 30 minutes, and applying the mixture to both sides of the roughened aluminum foil with a thickness of 20 μm, light-curing at room temperature for 1 hour to dry on the surface, and drying after 24 hours, and then hot-pressing the coated aluminum foil and the heat-sealing layer; bonding the outer nylon layer with the adhesive layer; and finally applying the above mixture to the outside of the nylon layer with a thickness of 3 μm, light-curing at room temperature for 1 hour to dry on the surface, and drying after 24 hours to obtain an aluminum-plastic film.
[0095] Example 2
[0096] The difference from Example 1 is:
[0097] (1) Preparation of silica sol: Silane coupling agent, ethyl orthosilicate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:30:30:10:0.5, and stirred and hydrolyzed for 60 minutes to obtain silica sol.
[0098] Preparation of titanium sol: silane coupling agent, tetrabutyl titanate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:40:20:10:0.5, and the titanium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0099] Preparation of zirconium sol: silane coupling agent, zirconium n-propoxide, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:30:30:10:0.5, and the zirconium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0100] (2) Preparation of silicon-titanium-zirconium composite sol: Weigh titanium sol, silica sol and zirconium sol in a mass ratio of 60:30:10, slowly add the titanium sol to the silica sol, stir evenly to obtain silicon-titanium sol, and then slowly add the zirconium sol intermediate to the silicon-titanium sol prepared above, stir evenly to obtain silicon-titanium-zirconium composite sol.
[0101] Example 3
[0102] The difference from Example 1 is:
[0103] (1) Preparation of silica sol: Silane coupling agent, ethyl orthosilicate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:25:35:10:0.5, and stirred and hydrolyzed for 60 minutes to obtain silica sol.
[0104] Preparation of titanium sol: silane coupling agent, tetrabutyl titanate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:35:25:10:0.5, and the titanium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0105] Preparation of zirconium sol: silane coupling agent, zirconium n-propoxide, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:25:35:10:0.5, and the zirconium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0106] (2) Preparation of silicon-titanium-zirconium composite sol: Weigh titanium sol, silica sol and zirconium sol in a mass ratio of 60:30:10, slowly add the titanium sol to the silica sol, stir evenly to obtain silicon-titanium sol, then slowly add the zirconium sol to the silicon-titanium sol prepared above, stir evenly to obtain silicon-titanium-zirconium composite sol.
[0107] Example 4
[0108] The difference from Example 1 is:
[0109] (1) Preparation of silica sol: Silane coupling agent, ethyl orthosilicate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:20:40:10:0.5, and stirred and hydrolyzed for 60 minutes to obtain silica sol.
[0110] Preparation of titanium sol: silane coupling agent, tetrabutyl titanate, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:30:30:10:0.5, and the titanium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0111] Preparation of zirconium sol: silane coupling agent, zirconium n-propoxide, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:30:30:10:0.5, and the zirconium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0112] (2) Preparation of silicon-titanium-zirconium composite sol: Weigh titanium sol, silica sol and zirconium sol in a mass ratio of 60:30:10, slowly add the titanium sol to the silica sol, stir evenly to obtain silicon-titanium sol, then slowly add the zirconium sol to the silicon-titanium sol prepared above, stir evenly to obtain silicon-titanium-zirconium composite sol.
[0113] Example 5
[0114] (1) Preparation of silica sol: Silane coupling agent, tetraethyl orthosilicate, anhydrous ethanol, and deionized water catalyst (specifically glacial acetic acid) in a mass ratio of 29.5:20:40:10:0.5 were mixed evenly, and stirred for hydrolysis for 60 minutes to obtain silica sol.
[0115] Preparation of titanium sol: silane coupling agent, tetrabutyl titanate, anhydrous ethanol, deionized water, and a catalyst (specifically glacial acetic acid) in a mass ratio of 29.5:30:30:10:0.5 were uniformly mixed, and the titanium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0116] (2) Preparation of silicon-titanium composite sol: Weigh titanium sol and silicon sol in a mass ratio of 70:30, slowly add the titanium sol to the silicon sol, and stir evenly to obtain a silicon-titanium composite sol.
[0117] (3) Weighing a silicon-titanium composite sol, a rare earth additive (specifically cerium nitrate), an acrylic resin, and an auxiliary agent (specifically a defoamer and a leveling agent) in a mass ratio of 85:4:10:1, slowly adding the rare earth additive, acrylic resin, and auxiliary agent into the silicon-titanium sol, stirring for 30 minutes, and applying the mixture to both sides of the roughened aluminum foil with a thickness of 20 μm, light-curing at room temperature for 1 hour to dry the surface, and drying after 24 hours, and then hot-pressing the coated aluminum foil and the heat-sealing layer; bonding the outer nylon layer with the adhesive layer; and finally applying the above mixture to the outside of the nylon layer with a thickness of 3 μm, light-curing at room temperature for 1 hour to dry the surface, and drying after 24 hours to obtain an aluminum-plastic film.
[0118] Example 6
[0119] (1) Preparation of silica sol: Silane coupling agent, tetraethyl orthosilicate, anhydrous ethanol, and deionized water catalyst (specifically glacial acetic acid) in a mass ratio of 29.5:20:40:10:0.5 were mixed evenly, and stirred for hydrolysis for 60 minutes to obtain silica sol.
[0120] Preparation of zirconium sol: silane coupling agent, zirconium n-propoxide, anhydrous ethanol, deionized water and catalyst were uniformly mixed in a mass ratio of 29.5:20:40:10:0.5, and the zirconium sol was obtained after stirring and hydrolyzing for 60 minutes.
[0121] (2) Preparation of silicon-zirconium composite sol: Weigh silicon sol and zirconium sol in a mass ratio of 75:25, slowly add the zirconium sol to the silicon-titanium sol prepared above, and stir evenly to obtain a silicon-zirconium composite sol.
[0122] (3) Weighing a silicon-zirconium composite sol, a rare earth additive (specifically cerium nitrate), an acrylic resin, and an auxiliary agent (specifically a defoamer and a leveling agent) in a mass ratio of 85:4:10:1, slowly adding the rare earth additive, acrylic resin, and auxiliary agent into the silicon-titanium sol, stirring for 30 minutes, and applying the mixture to both sides of the roughened aluminum foil with a thickness of 20 μm, light-curing at room temperature for 1 hour to dry on the surface, and drying after 24 hours, and then hot-pressing the coated aluminum foil and the heat-sealing layer; bonding the outer nylon layer with the adhesive layer; and finally applying the above mixture to the outside of the nylon layer with a thickness of 3 μm, light-curing at room temperature for 1 hour to dry on the surface, and drying after 24 hours to obtain an aluminum-plastic film.
[0123] Comparative Example 1
[0124] The commercially available aluminum-plastic film comprises a nylon outer layer, an outer adhesive layer, an Al outer treatment layer, an aluminum foil layer, an Al inner treatment layer, an inner adhesive layer and a polypropylene layer which are stacked in sequence.
[0125] Comparative Example 2
[0126] The difference from Example 1 is that the corrosion-resistant coating does not contain Si element.
[0127] Comparative Example 3
[0128] The difference from Example 1 is that the corrosion-resistant coating is an acrylic resin layer.
[0129] Comparative Example 4
[0130] The difference from Example 1 is that the corrosion-resistant coating is an acrylic resin layer containing Si element.
[0131] Performance Testing
[0132] (1) Wear resistance test: Tested in accordance with GB / T 6739-2006.
[0133] (2) Strength test: Tested in accordance with GB / T 1732-93.
[0134] (3) Flexibility test: Tested in accordance with standard GB / T 1731-1993.
[0135] (4) Contact angle test: 5 μL (5 μL per drop) of ethylene glycol was added to the surface of the corrosion-resistant coating of the aluminum-plastic film of each embodiment and comparative example using a microsyringe, and the surface contact angle was calculated using a five-point fitting method. The obtained contact angle was the average of the five contact angles measured. When the contact angle was >90°, it indicated that the aluminum-plastic film was oleophobic, and when it was <90°, it indicated that the aluminum-plastic film was oleophilic.
[0136] (5) Corrosion resistance test: The aluminum-plastic films of Examples 1-6 and Comparative Examples 1-4 were made into aluminum-plastic film bags, with the side surface having the heat-sealing layer as the inner surface of the aluminum-plastic film bags, and the same electrolyte of the same content was injected into the bags. The bags were placed in an environment of 200° C. for an accelerated test, and then the aluminum foil in the aluminum-plastic film was separated using an aluminum-plastic film stripping liquid. The separated aluminum foil was then placed on a coordinate paper (with a coordinate interval of 1 cm*cm), and photographed using a digital camera. The actual size of 3 cm*2 cm was uniformly captured, and then the software was used to further process the images (3 cm*2 cm) and the pixels of the corrosion area. Finally, the corrosion area was calculated; wherein,
[0137] The corrosion area calculation formula is: (corrosion area pixels / image pixels)*3cm*2cm. The results are summarized in Tables 1 and 2.
[0138] In the above tests, two samples were taken from each embodiment or comparative example of the aluminum-plastic film for testing.
[0139] Table 1
[0140]
[0141] Table 2
[0142]
[0143] Combining the data in Table 1 and Table 2, it can be found that the corrosion resistance of the aluminum-plastic film provided in the embodiment of the present application is significantly better than that of the comparative example, and the hardness, flexibility and high-temperature electrolyte immersion resistance of the aluminum-plastic film of the embodiment have reached the use standard, and have a certain oleophobicity; and when the corrosion-resistant layer of the aluminum-plastic film contains Si element, Ti element and Zr element at the same time (Example 1-Example 4), the corrosion resistance effect is stronger.
[0144] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. An aluminum-plastic film, characterized in that: It comprises an aluminum foil and a corrosion-resistant coating arranged on at least one side of the aluminum foil; the corrosion-resistant coating comprises an A element, and the A element is selected from at least one of a Ti element and a Zr element and an Si element.
2. The aluminum-plastic film according to claim 1, characterized in that: The corrosion-resistant coating further comprises a resin; The resin includes one or more of acrylic resin, polyurethane resin, fluorocarbon resin and epoxy resin.
3. The aluminum-plastic film according to claim 2, characterized in that: The mass proportion of the resin in the corrosion-resistant coating is 5wt% to 15wt%.
4. The aluminum-plastic film according to claim 2 or 3, characterized in that: The corrosion-resistant coating includes a compound containing an AOA bond, and a chemical bond is formed between the compound containing an AOA bond and the resin; the AOA bond includes at least one of a Si-O-Ti bond and a Si-O-Zr bond and a Si-O-Si bond.
5. The aluminum-plastic film according to any one of claims 1 to 4, characterized in that: The A element includes Zr element and Si element.
6. The aluminum-plastic film according to any one of claims 1 to 5, characterized in that: The aluminum-plastic film includes a plurality of the corrosion-resistant coatings, and the aluminum foil includes a first surface and a second surface that are arranged opposite to each other; The plurality of corrosion-resistant coatings include a first corrosion-resistant coating and a second corrosion-resistant coating; wherein the first corrosion-resistant coating is disposed on the first surface, and the second corrosion-resistant coating is disposed on the second surface; The first corrosion-resistant coating includes a Zr element, and a mass content of the Zr element in the first corrosion-resistant coating is greater than a mass content of the Zr element in the second corrosion-resistant coating.
7. The aluminum-plastic film according to claim 6, characterized in that: The first corrosion-resistant coating comprises Ti, Zr and Si elements; in the first corrosion-resistant coating, the mass proportion of the Zr element is 0.3wt% to 1.5wt%, the mass proportion of the Ti element is 1.27wt% to 3wt%, and the mass proportion of the Si element is 0.28wt% to 2.5wt%; and / or, The second corrosion-resistant coating includes Ti element, Si element and optionally Zr element; in the second corrosion-resistant coating, the mass proportion of the Zr element is 0-1.3wt%, the mass proportion of the Ti element is 1.27wt%-3wt%, and the mass proportion of the Si element is 0.28wt%-2.5wt%.
8. The aluminum-plastic film according to claim 6 or 7, characterized in that: The aluminum-plastic film further comprises a nylon layer; the nylon layer is arranged between the first corrosion-resistant coating and the aluminum foil.
9. The aluminum-plastic film according to claim 8, characterized in that: The aluminum-plastic film further comprises a third corrosion-resistant coating; the third corrosion-resistant coating is arranged between the nylon layer and the aluminum foil; The third corrosion-resistant coating comprises Ti element, Si element and optionally Zr element; In the third corrosion-resistant coating, the mass proportion of the Zr element is 0-1.3wt%, the mass proportion of the Ti element is 1.27wt%-3wt%, and the mass proportion of the Si element is 0.28wt%-2.5wt%.
10. The aluminum-plastic film according to any one of claims 7 to 9, characterized in that: The thickness of the first corrosion-resistant coating is 1 μm-5 μm, and the thickness of the second corrosion-resistant coating is 20 μm-30 μm.
11. The aluminum-plastic film according to claim 9, characterized in that: The thickness of the third corrosion-resistant coating is 20 μm-30 μm.
12. The aluminum-plastic film according to claim 9 or 11, characterized in that: An adhesive layer is provided between the first corrosion-resistant coating and the nylon layer, and between the third corrosion-resistant coating and the nylon layer.
13. A method for preparing an aluminum-plastic film, characterized in that: include: Mixing a Ti element source and / or a Zr element source, a silane coupling agent, and water to obtain a mixture; The mixture is formed on at least one side surface of an aluminum foil and cured to form a corrosion-resistant coating to obtain an aluminum-plastic film.
14. The preparation method according to claim 13, characterized in that: The Ti element source includes one or more of tetrabutyl titanate, tetraethyl titanate, and tetraisopropyl titanate; and / or, The Zr element source includes one or more of zirconium n-propoxide, zirconium n-butoxide, zirconium tert-butoxide, and zirconium tetraethoxide.
15. The preparation method according to claim 13 or 14, characterized in that: The mixing also includes adding resin raw materials.
16. The preparation method according to claim 15, characterized in that: The mixing also includes adding a first silicon source, wherein the first silicon source includes one or more of tetraethyl orthosilicate, silicate, and organic silane polymer.
17. The preparation method according to claim 16, characterized in that: Based on the total mass of the mixture, the mass proportion of the silane coupling agent is 15.2wt%-27wt%, the mass proportion of the water is 2.3wt%-13.5wt%, the sum of the masses of the Ti element source and the Zr element source is 38wt%-63wt%, the mass proportion of the resin raw material in the mixture is 5wt%-15wt%, and the mass proportion of the first silicon source in the mixture is 3wt%-9.5wt%.
18. A battery, characterized in that: The invention comprises an aluminum-plastic film, wherein the aluminum-plastic film is the aluminum-plastic film according to any one of claims 1 to 12, or the aluminum-plastic film is obtained by the preparation method of the aluminum-plastic film according to any one of claims 13 to 17.
19. An electrical equipment, characterized in that: The electrical device comprises the battery according to claim 18.
Citation Information
Patent Citations
Surface-oleophobic aluminum plastic film for packaging lithium battery and preparation process of surface-oleophobic aluminum plastic film
CN104466039A
Preparation method of organic-inorganic composite sol for metal aluminum sheet surface corrosion prevention
CN104559351A
Anticorrosive coating of titanium sol modified aluminum electrode and preparation method thereof
CN105820607A
Package material for electricity storage device, and method for manufacturing package material for electricity storage device
CN108140751A
Electrolyte-resistant and anti-stripping aluminum plastic film, preparation method thereof and battery
CN113036271A
